2018
DOI: 10.1177/2165079918790585
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Psychological Well-Being in Older University Office Workers: Survey Findings

Abstract: Prolonged sitting time has been reported among university workers which can have adverse health effects. The aim of this study was to examine the sitting time, physical activity, and psychological well-being reported by older university office workers. An online self-reported survey was distributed to all office workers 55 years and older at one university in Australia. Sixty-six office workers were recruited. They reported an average sitting time of 7.5 hours per day on weekdays. In all, 72.7% of the sample r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The current study also found that people with a bachelor or TAFE/college qualification had lower levels of perceived stress compared with those with only a high school qualification. Qi et al [27] concluded that educated people may have relevant knowledge in accessing appropriate resources and selecting effective strategies to eliminate negative moods and manage their stress symptoms. Thus, relevant online educational programs may have the potential to reduce people's levels of perceived stress during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also found that people with a bachelor or TAFE/college qualification had lower levels of perceived stress compared with those with only a high school qualification. Qi et al [27] concluded that educated people may have relevant knowledge in accessing appropriate resources and selecting effective strategies to eliminate negative moods and manage their stress symptoms. Thus, relevant online educational programs may have the potential to reduce people's levels of perceived stress during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high emotional pressures that workers experience and the prolonged duration of their workday, many of them lack physical activity [56], thus generating adverse effects such as musculoskeletal disorders [57], obesity [58], and diabetes [59].…”
Section: Impact Of Emotional Well-being On Physical Well-beingmentioning
confidence: 99%
“…Due to the experience of prolonged sitting during working hours as well as work-related physical impairments, psychological issues, and chronic pain among older office workers, there is a need to pay more attention to this population. Hence, older office workers in this study are defined as academic and administrative staff aged 55 years and older who are employed by universities [12]. In order to inform the development of an appropriate workplace intervention that will positively affect the health of university office workers 55 years and older in China and Australia, the aim of this study was, therefore, to use an online survey to investigate the levels of physical activity participation, stress, depression, anxiety, and pain as well as the sitting time of university office workers from China and Australia in order to explore: (1) the differences in physical activity, sedentary time, and psychological wellbeing of university office workers over 55 years between the two countries; (2) the associations between the demographic characteristics and psychological wellbeing in the two countries; and (3) the associations between physical activity participation and sitting time and psychological wellbeing in the two countries.…”
Section: Introductionmentioning
confidence: 99%
“…As for symptoms of anxiety and depression, a higher percentage of university staff showed clinical scores of anxiety and depression compared with the general population [ 11 ]. Almost half of the university office workers in Australia reported headache and neck pain in one of our previous studies [ 12 ]. Thus, of the international research to date on the physical activity and psychological health of university employees, studies have focused on sedentary sitting time, psychological wellbeing (e.g., stress, depression, and anxiety), and pain issues.…”
Section: Introductionmentioning
confidence: 99%